2021
DOI: 10.3390/jtaer16070183
|View full text |Cite
|
Sign up to set email alerts
|

Deploying Big Data Enablers to Strengthen Supply Chain Agility to Mitigate Bullwhip Effect: An Empirical Study of China’s Electronic Manufacturers

Abstract: With the development of economic globalization, the uncertainty of supply chains is also increasing, and alleviating the bullwhip effect has become an important issue. From previous discussions on alleviating the bullwhip effect, there was no research on alleviating it by enhancing supply chain agility through improving big data. Moreover, it has not been found that quality function deployment is used to analyze the interdependence between big data and supply chain agility, as well as between supply chain agil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…Big data has become increasingly important in supply chain management, offering opportunities for innovation and risk mitigation. Case studies have shown that the application of big data analytics in supply chain operations can enhance innovation capabilities, reduce operating costs, improve flexibility, and enhance customer satisfaction (Tan et al, 2015;Hsu et al, 2021). However, the integration of big data analytics with sustainability to mitigate supply chain risk has been slow to achieve desired outcomes (Mani et al, 2017).…”
Section: Case Studies Of Reviewing the Use Of Big Data In Supply Chai...mentioning
confidence: 99%

Reviewing the use of big data in supply chain optimization in the USA

Israel Osejie Okoduwa,
Bankole Ibrahim Ashiwaju,
Jeremiah Olawumi Arowoogun
et al. 2024
World J. Adv. Res. Rev.
“…Big data has become increasingly important in supply chain management, offering opportunities for innovation and risk mitigation. Case studies have shown that the application of big data analytics in supply chain operations can enhance innovation capabilities, reduce operating costs, improve flexibility, and enhance customer satisfaction (Tan et al, 2015;Hsu et al, 2021). However, the integration of big data analytics with sustainability to mitigate supply chain risk has been slow to achieve desired outcomes (Mani et al, 2017).…”
Section: Case Studies Of Reviewing the Use Of Big Data In Supply Chai...mentioning
confidence: 99%

Reviewing the use of big data in supply chain optimization in the USA

Israel Osejie Okoduwa,
Bankole Ibrahim Ashiwaju,
Jeremiah Olawumi Arowoogun
et al. 2024
World J. Adv. Res. Rev.
“…Therefore, it is vital to explore the relationship between big data and supply chain agility. Most existing studies only confirm that big data has a positive impact on supply chain agility (Hsu et al, 2021;Wamba et al, 2020). However, these studies are insufficient.…”
Section: Big Data and Supply Chain Agilitymentioning
confidence: 99%